Determinants of accidental falls and fall-related injuries. Recommendations for falls and fall-related injuries prevention set on the analysis of a theoretical dynamic system involving the older adult, the environment and the task performance. - Pereira, Catarina (2015)
This work aims to provide easy and practical recommendations for falls and fall-related injuries prevention set on the analysis of a theoretical dynamic system involving the subject (older adult), the environment, and the task performance. In accordance with this system, accidental falls occur while performing physical activities/tasks. In the absence of movement the probability of falling will be almost zero. However, immobility decreases the subject´s ability of performance. The fall usually occurs when the demands of a given task exceed the subject’s ability. The demands of a task are determined by its difficulty and by environmental conditions. In a hostile environment, the demands of a given task increase. As result, the task demands may exceeds the subject’s ability causing a fall. The ability to perform daily tasks without falling tends to decline with age due to associated frailty (notably the increased morbidities and the diminished physical, sensorial, and neural fitness). However, falls may also be a problem before the age of 60 years. The main immediate consequence of a fall is injury, which may be fatal. Another possible short-term consequence is an increased fear of falling that often conducts to a loss of independence while performing daily tasks and, consequently, leads to a decline in the subject’s ability. It was observed that the determinant factor for the rupture of this system balance (resulting in falls and fall-related injuries) in older adults is the subject, namely his/her condition of frailty. As the subject becomes more fragile and as the risk of intrinsic factors increases, their susceptibility to extrinsic factors rises, especially with regard to environmental hazards. Thereafter, the subject’s likelihood of falling and injuring increases. However, a good level of physical fitness can also increase the threat of falling and injuring, because fitter people are more confidence in performing more demanding tasks and in more hazardous environments. Thereby, they expose themselves to more dangerous situations. Given the above and reporting recent research findings, the primary recommendations for fall and fall-related injuries prevention are the following: • A healthy lifestyle, in order to avoid co-morbidities or, at least, to minimize its effects. • The reduction of environmental hazards, principally when fitness decreases and frailty increases, and the restraint of difficult tasks in hazardous environments. • The practice at least 1,150 MET-min.wk-1 of physical activity, with no more than 500 MET-min.wk-1 (~60 min. wk-1) of vigorous physical activity (due to associated hazards). For example a combination of 1 hour of walking, 2 hours of moderate physical activity (such as carrying light loads or bicycling at a regular pace) and 20 minutes of vigorous physical activity (such as heavy lifting, digging, aerobics, or fast bicycling) per week, what computes ~1,150 MET-min.wk-1. • The implementation of exercise programs to prevent physical fitness loss, especially balance. Further, muscle strength and gait exercises may be particularly relevant for less fit and frail people. • The performance of functional exercises that mimic everyday life tasks and promote self-confidence. • Regarding women, special attention must be taken because they tend to be more fragile. Regarding men, special attention must be taken because they tend to expose themselves to more hazardous situations.